Weight status change during four years and left ventricular hypertrophy in Chinese children - Liu, Qin; Li, Cheng; Yang, Lili; Gong, Zhuo; Zhao, Min; Bovet, Pascal; Xi, Bo (Frontiers in Pediatrics, 2024)
Objective: It is well-established that overweight/obesity is a major risk factor for left ventricular hypertrophy (LVH) in childhood. However, it is still unclear if reversing from overweight/obesity to normal weight is associated with decreased LVH in children. This study aimed to examine the association between weight status change during four years and LVH among Chinese children based on a prospective cohort study. Methods: Data were obtained from the Huantai Childhood Cardiovascular Health Cohort Study in China. A total of 1178 children without LVH at baseline (mean age: 8.3 years) were included in this study. According to weight status (normal weight or overweight [including obesity]) at baseline (2017) and follow-up (2021), children were divided, based on sex-and age-adjusted body mass index (BMI), into four groups: persistent normal weight (normal weight at both baseline and follow-up), incident overweight (normal weight at baseline but overweight at follow-up), reversal to normal weight (overweight at baseline but normal weight at follow-up), persistent overweight (overweight at both baseline and follow-up).Results: After adjustment for potential confounding factors, children with incident overweight (n=114, 30.63 ± 4.74 g/m 2.7 ) and those with persistent overweight (n=363, 31.56 ± 6.24 g/m 2.7 ) had higher left ventricular mass index (LVMI) at the end of the follow-up period than those with persistent normal weight (n=632, 28.46 ± 7.64 g/m 2.7 ), while those who reversed from overweight to normal weight had a non-significantly lower LVMI (n=69, 28.51 ± 4.28 g/m 2.7 ). Compared to children with persistent normal weight, those with persistent overweight (odds ratio [OR] = 5.14, 95% confidence interval [CI] = 3.33-7.95) and those with incident overweight (OR = 3.34, 95% CI = 1.77-6.30) had an increased risk of LVH. The risk of LVH tended to decrease, although not significantly, in those who reversed from overweight to normal weight (OR = 0.76, 95% CI = 0.22-2.55).Our findings demonstrate a positive association between overweight and left ventricular mass in children and suggest that LVH in childhood could be attenuated by weight loss.